Mitochondrial and sarcoplasmic protein changes in hearts from copper deficient rats: Upregulation of PGC1-α transcript and protein as a cause for mitochondrial biogenesis in copper deficiency - Medeiros, Denis M.; Jiang, Yu; Klaahsen, Darcey; Dingbo, Lin (My University, 2009)
Changes in mitochondrial and sarcoplasmic proteins using proteinomics and western blotting in hearts from copper deficient rats were explored in this study. Also, key enzymes that are involved in cardiac energy metabolism via glycolysis and fatty acid oxidation and related transcription factors were determined. Rats were fed one of two diets: a copper adequate diet containing 6 mg Cu/kg diet or a diet with less than 1 mg Cu/kg diet for 5 weeks. Copper deficiency was confirmed by low liver copper levels, decreased hematocrit levels, and cardiac hypertrophy. Proteinomic data revealed that of the more than 50 proteins identified from the mitochondrial fraction of heart tissue, 6 were significantly down regulated and 9 were upregulated. The proteins that were decreased were beta enolase 3, carbonic anhydrase 2, aldose reductase1, glutathione peroxidase, muscle creatine kinase, and mitochondrial aconitase 2. The proteins that were up-regulated were isocitrate dehydrogenase, dihydrolipoamide dehydrogenase, transferrin, subunit d of ATP synthase, transthyretin, preproapolipoprotein A-1, GRP 75, alpha-B crystalline, and heat shock protein alpha. Follow-up western blots on rate limiting enzymes in glycolysis (phosphofructose kinase), fatty acid oxidation (medium chain acyl dehydrogenase, peroxisome proliferator-actvator receptor-α or PPARα), and gluconeogenesis (phosphoenolpyruvate carboxykinase), did not reveal changes in metabolic enzymes. However, a significant increase in peroxisome proliferator-activated receptor- coactivator (PGC)-1α protein, as well as the transcript, which increased 2.5 fold were observed. It would appear that increased mitochondrial biogenesis known to occur in copper deficiency hearts is caused by an increase expression in the master regulator of mitochondrial biogenesis, PGC-1α.
Keywords: Proteinomics; Copper deficiency; Rats; PGC-1α; Metabolic enzymes